System Dynamic Modeling for Terrorism Considering Infiltration - Hennie Husniah,*, R. A. R. Harry Anwar, Deni Haspada, Davidescu C. Victoria, Asep K. Supriatna (International Journal of Advanced Science and Technology, 2020)
This article aims to show the development of a terrorism model through a dynamic systemapproach in a human population. The authors consider that the underlying population isdivided into three categories, namely terrorists, pacifists, and those who are easilyinfluenced by both terrorist and pacifist propaganda. The dynamic behavior of the threesubpopulations is represented using three differential equations. These differentialequations show the growth of the three subpopulations. The model takes into account theimpact of direct military / police interventions in order to reduce the terroristsubpopulation, and nonviolent, persuasive interventions to influence vulnerable people tobe pacifists. The authors also look at the effect of infiltration as another intervention onthe terrorist population. Moreover, the authors present numerical examples to illustratesystem behavior and some important features resulting from the proposed dynamic model.One of the important features is that the effect of military / police interventions issignificantly affected by the characteristics of the system, which is represented by thevalues of the parameters in the model. The effectiveness of terrorists to attractsusceptibles to become new members, which is often called as the force of influence, isamong the parameters that influences the effect of the intervention. We simulate variousscenarios for different values representing low, medium, and high force of influence. Abroad insight into how to design appropriate terrorism management in a scientific way isalso presented.